Actual tasks of choreographic training in gymnatic sports - Todorova, V. H.; Pogorelova, O. O.; Kashuba, V. O. (International Journal of Applied Exercise Physiology, 2020)
Introduction: Modern rules of competition place extremely high requirements on the choreographic preparation of athletes in various gymnastic kind of sport. These requirements apply to both the technique and the artistry of the exercises. In gymnastic kind of sport with high requirements for choreographic preparation, two different teams of judges are involved in the evaluation of the "technical" and "artistic" components, the ratings of which equally influence on the result of the athletes' competitive activity. Objective: The aim of this work was to identify directions for improving choreographic training in gymnastic sports. Interviews were conducted with 50 experts in rhythmic gymnastics, sport gymnastics, sport acrobatics, bouncing on trampoline, sport aerobics, that certifies the lack of a unified approach to the methodology and organization of choreographic training at different stages of long-term improvement of sportsmen. Methods: analysis of special theoretical and science methodological literature, documentary materials, rules of competitions in gymnastic sports that are part of the International Federation of Gymnastics (FIG); sociological methods; including surveys; pedagogical: experiment, conversation, mathematical statistics. Results: Unanimously defining the need for quality and effective choreographic training, coaches pay attention to the lack of adapted choreography facilities that meet current trends and requirements of the sport, competition rules and features of the technique of performing choreographic and specific elements of sport. Conclusion: According to the coaches, one of the ways of improving the technique of choreographic training in gymnastic sports should be strengthening the work on the technique of performing choreographic exercises and elements inherent in the sport. In order to achieve this, it is necessary to improve the program material on choreographic training, organize it in accordance with current trends of development and features of the sport, introduce the necessary control over the level of choreographic fitness of athletes.